TINDAK PIDANA PUNGUTAN LIAR MENURUT UNDANG-UNDANG NOMOR 31 TAHUN 1999 DI KOTA BAUBAU - Hardi Done; Samaluddin Samaluddin; Aldi Nizar Setiawan (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2021)
In 2016, Presidential Regulation Number 87 of 2016 concerning Units to Sweep Clean Illegal Levies was issued, and was supported by the issuance of the Circular of the Minister of State Apparatus Empowerment for Bureaucratic Reform Number 5 of 2016 concerning the Eradication of Illegal Levies Practices in the Implementation of Duties and Functions of Government Agencies. According to the view point of the formation of laws, a rule is made to protect the interests of individuals and society. With the issuance of Presidential Regulation Number 87 of 2016, it is hoped that it can cleanly eradicate extortion cases that often occur in the community, especially aimed at state apparatus officials in serving the community well. The success of eradicating extortion, which is included in the category of corruption, will have a widespread positive impact on the people, nation and state, because the practice of extortion shows a corrupt, rotten and lecherous, dishonest act that is linked to finances. In this case, the Attorney General's Office as one of the state institutions has the authority to carry out investigations regarding whether or not there are criminal acts and resolve cases of extortion by state apparatus officials in order to create security and public comfort. This research uses field research, the data collection technique of this research is by interviewing. Head of the UPTD Ferry Baubau Port of Crossing. This research uses normative and empirical research types, as well as primary and secondary data sources where conducting research by means of interviews, namely going directly to the field.